Homestead gardening: A gender-responsive solution for a resilient and food-secure Bangladesh - Sarker, Mou Rani; Humaira, Bushra; Ahmed, Sharif; Bhandari, Humnath (International Rice Research Institute, 2025)
Homestead gardening (HG) offers a practical, low-cost, and gender-responsive way to improve nutrition and build resilience, especially in climate-stressed regions. With support from the International Rice Research Institute (IRRI) under the CGIAR Program on Scaling for Impact, homestead gardening is being introduced and scaled in parts of Patuakhali, Rangpur, and Nilphamari, where households face both climate and nutrition challenges.